Women's entrepreneurial leadership on culinary micro small medium enterprises success: The mediating role of absorptive capacity - Leonita Siwiyanti; Suryana Suryana; Chairul Furqon; Heny Hendrayati; Frederic Marimon (Universitas Ahmad Dahlan, 2025)
In many developing economies, culinary businesses run by women face dynamic market challenges that demand adaptive leadership and effective knowledge utilization. This study explores the influence of women’s entrepreneurial leadership on the business success of micro, small, and medium enterprises in the culinary sector with absorptive capacity as a mediating factor. A survey method was used to gather quantitative data from 350 women entrepreneurs, and partial least squares structural equation modeling was used for statistics analysis. The results show that women's leadership qualities, such as empathy, teamwork, and flexibility, significantly improve company performance. Additionally, absorptive capacity serves a critical mediating function by allowing entrepreneurs to obtain, absorb, and apply outside knowledge for innovation and market adaptation. The study emphasizes how crucial it is to support women's entrepreneurial leadership and knowledge-absorption skills to promote long-term company growth. These findings provide valuable insights for policymakers, educators, and business practitioners in designing targeted interventions to support women entrepreneurs in resource-constrained environments.